Temporal bone involvement of IgG4-related disease: A rare condition misleading to petrous apicitis causing lateral rectus palsy - Sanathorn Chowsilpa (2019)
© 2019 BMJ Publishing Group Limited. No commercial re-use. See rights and permissions. Published by BMJ. IgG4-related disease (IgG4-RD) of temporal bone is rare and clinical manifestation mimics infection. A 19-year-old female presented with progressive left earache and intermittent left nasal obstruction. Then, she rapidly developed left lateral rectus palsy. The physical examination revealed mild redness of left tympanic membrane and a small nasal polyp from the left middle meatus. CT scan showed left petrous apicitis and enhancing sinonasal mucosa. Therefore, Gradenigo's syndrome was first considered. The empirical intravenous antibiotic was immediately prescribed and surgery was performed. The intraoperative pale soft tissue mass in middle ear and polyp in the left nasal cavity were sent for pathological examination and found positive immunohistochemical stains for IgG4 in plasma cells. Systemic corticosteroid, the first-line treatment, was started and her symptoms were finally recovery.